2018
DOI: 10.1186/s40425-018-0452-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell-released autophagosomes (TRAPs) promote immunosuppression through induction of M2-like macrophages with increased expression of PD-L1

Abstract: BackgroundTumor-associated macrophages (TAMs) facilitate tumor progression via establishment of an immunosuppressive tumor microenvironment (TME). However, it is poorly understood how tumor cells could functionally modulate TAMs. Our previous work indicated that tumor cell-released autophagosomes (TRAPs), a type of LC3-II+ double-membrane extracellular vesicles (EVs) was sufficient to suppress anti-tumor immune responses by inducing IL-10-producing B cells and immune suppressive neutrophils. Here, we hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 53 publications
3
90
2
Order By: Relevance
“…In good agreement, we found that both stromal and tumor-infiltrating M2 macrophages were associated with PD-L1 expression, which was previously associated with poor prognosis in OSCC [ 19 ]. Experimental studies have reported that tumor cells can induce M2 macrophage phenotype increasing the expression of PD-L1 [ 41 ]. In fact, PD-L1 expression is induced after exposure to interferon-γ (IFN-γ) released by T effector cells, as well as after other signals such as TNF-α, VEGF, and CXCL8, ultimately promoting lung cancer progression [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In good agreement, we found that both stromal and tumor-infiltrating M2 macrophages were associated with PD-L1 expression, which was previously associated with poor prognosis in OSCC [ 19 ]. Experimental studies have reported that tumor cells can induce M2 macrophage phenotype increasing the expression of PD-L1 [ 41 ]. In fact, PD-L1 expression is induced after exposure to interferon-γ (IFN-γ) released by T effector cells, as well as after other signals such as TNF-α, VEGF, and CXCL8, ultimately promoting lung cancer progression [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…And HLA-DR as a key marker has been used to distinguish M1 macrophages from M2 macrophages [27,28]. Suggest HLA-DR deletion may be a molecular mechanism that mediates M2 [29,30]. Suggesting the loss of macrophage HLA-DR mediates immune escape and is an upstream molecular event that leads to M2 macrophage polarization.…”
Section: Low Expression Of Hla-dr Positively Correlated With High-denmentioning
confidence: 99%
“…The regulation of PD-L1 expression in cancer is complex. In addition to inflammatory factors such as IL-10 and GM-CSF (21), other factors such as tumor cell-released autophagosomes (TRAPs) (29), long non-coding RNA HOXA transcript at the distal tip (HOTTIP) (30), and IL-6 from cancer-associated fibroblasts (CAFs) (31) have also been reported to regulate PD-L1 expression. Recently, EVs have been identified as an important factor to induce PD-L1 expression and impair antitumor immune.…”
Section: Discussionmentioning
confidence: 99%